Intention to purchase the Body Shop among Indonesian consumers: An application of the Theory of Planned Behavior - Ainun Ainiyah; Yudi Sutarso (SEAN Institute, 2022)
The Theory of Planned Behavior has been one of the focuses in academia for research. However, the complex process regarding purchase behavior on well-being skincare and the cosmetic product is sparse. This study aims to apply the Theory of Planned Behavior (TPB) model using its core constructs to predict consumers’ purchase behavior of well-being products, namely the Body Shop. Questionnaires were gathered using a convenient purposive and non-probability technique. A total of 130 respondents were used for data analysis. The method from the distributed questionnaire consumers in Indonesia. The software package was used by SPSS 26 and Wrap PLS 7.0. The results of the study all hypotheses are significant. Based on the results, theoretical and practical implications were suggested